"A Field Study of the Effect of Perceived Organizational Support on Affective Organizational Commitment: The Mediating Role of Role Ambiguity in the Presence of Perceived Supervisor Support and Agreeableness in the Egyptian Textile and Garments Companies - Atteya, Ghada (The Arab Journal of Administration, 2022)
Perceived Organizational Support (POS) exists when employees develop global beliefs concerning the extent to which the organization values their contributions, cares about their well-being and reward their increased work effort. Although there is a growing research concerning antecedents and consequences of Perceived Organizational Support, still there is a need to identify the mechanisms and conditions through which Perceived Organizational Support may affect the subordinates’ behaviors. Relying on Social Exchange and Organizational Support theories, the present study aims to investigate the relationship between Perceived Organizational Support and Affective Organizational Commitment through Role Ambighuity (as a mediator). It also seeks to identify the conditions in which Perceived Organizational Support would be more influential on the followers’ behaviors, through studying Perceived Supervisor Support, and Agreeableness (as Moderators). Using the Mediated and Moderator Regression Analyses, on a sample of 446 employees, working in the Textile and Garments Sector in Alexandria, the results confirmed the hypothesees, and showed that Role Ambighuity (as a type of Hindrance Stressors) partially mediated the relationship between Perceived Organizational Support and Affective Commitment, in which Perceived Organizational Support positively affects Affective Commitment through reducing employees’ perceptions of Role Ambiguity. In addition, the inverse relationship between Perceived Organizational Support and Role Ambiguity became stronger in condition of the interaction between Perceived Organizational Support and Perceived Supervisor Support, and Agreeableness.